2010
DOI: 10.1371/journal.pone.0008654
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Structural Analysis of the Chitinase Insertion Domain Reveals Two Conserved Motifs Involved in Chitin-Binding

Abstract: BackgroundChitinases are prevalent in life and are found in species including archaea, bacteria, fungi, plants, and animals. They break down chitin, which is the second most abundant carbohydrate in nature after cellulose. Hence, they are important for maintaining a balance between carbon and nitrogen trapped as insoluble chitin in biomass. Chitinases are classified into two families, 18 and 19 glycoside hydrolases. In addition to a catalytic domain, which is a triosephosphate isomerase barrel, many family 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 79 publications
(131 reference statements)
4
93
0
4
Order By: Relevance
“…The characteristic catalytic domain is called the glycosyl hydrolase (GH) domain, which consists of about 220 to 230 amino acid residues (Liu et al, 2010). The catalytic domain is grouped into two families: glycosyl hydolase family 18 (GH18) and glycosyl hydrolase family 19 (GH19) (Li and Greene, 2010). Chitinases belong to the GH18 family including class III and V chitinases (Takenaka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic catalytic domain is called the glycosyl hydrolase (GH) domain, which consists of about 220 to 230 amino acid residues (Liu et al, 2010). The catalytic domain is grouped into two families: glycosyl hydolase family 18 (GH18) and glycosyl hydrolase family 19 (GH19) (Li and Greene, 2010). Chitinases belong to the GH18 family including class III and V chitinases (Takenaka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1) that function to allow the enzyme access to tightly packed chitin and assist in catalysis. 13) Members of the family GH-18 chitinase subfamily A have an extra domain with a small α + ÎČ domain (chitinase insertion domain, CID) inserted into the core TIM-barrel fold, 8,11,40) while chitinase subfamilies B and C have no such domain. 7,8,41) BLAST 27) and ClustalW 28) analysis revealed that the amino acid sequence of the 1st GH-18 domain was 56% identical to the 2nd GH-18 domain; 42% identical to the catalytic domain of chitinase A1 from Bacillus circulans WL-12, 40) belonging to subfamily A judged by its primary and three dimensional structures; 11% identical to catalytic domains of chitinase from Bacillus cereus NCTU2, belonging to subfamily B also based on its primary and three dimensional structures 41) ; and 10% identical to chitinase C1 from Serratia marcescens 2170, which belongs to subfamily C based on its amino acid sequence 7) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6) The bacterial chitinases of family GH-18 are classified into three subfamilies: A, B, and C. 7,8) The GH-18 chitinases have a triosephosphate isomerase (TIM-barrel) fold as a catalytic domain and have a retaining mechanism, 9) while the GH-19 chitinases are comprised of lysozyme-like (α + ÎČ)-folds and use an inverting mechanism. 10) Some chitinases are multi-modular in structure, composed of more than one functional domain, such as a catalytic domain and a carbohydrate binding module (CBM) to bind and assist in long chitin chain degradation.…”
mentioning
confidence: 99%
“…Chitinases are typified by the presence of a glycosyl hydrolase domain which corresponds to the catalytic domain. The chitinase family can be subdivided into two main groups-glycoside hydrolase family 18 (GH 18) and glycoside hydrolase family 19 (GH 19)-based on differences in this domain (Davies and Henrissat 1995;Iseli et al 1996;Li and Greene 2010). Biochemically, chitinases are grouped into classes I to VII, based on their primary structure and the presence of one or more diagnostic motifs (Collinge et al 1993;Neuhaus 1999;Grover 2012).…”
Section: Introductionmentioning
confidence: 99%